Kandungan klorofil dan karotenoid Kacang Tunggak (Vigna unguiculata (L.) Walp.) pada umur tanaman yang berbeda - Ika Susanti Hendriyani; Yulita Nurchayati; Nintya Setiari (Jurnal Biologi Tropika, 2018)
Chlorophyll is a pigment of photosynthesis which is also efficacious as a cure for brain, lung, and oral cancer, and can be used as a disinfectant, antibiotic and dietary supplement, while carotenoids are useful as antioxidants. The content of the two pigments is strongly influenced by the age of the plant, especially for vegetable crops used in leaves such as cowpea (Vigna unguiculata (L.) Walp.). The purpose of this research is to know the pattern of chlorophyll content and carotenoid of cowpea leaf during the growth phase and to know the age of the right plant for harvesting cowpea so that the highest chlorophyll and carotenoid content is obtained. Cowpea seeds obtained from seeds are added then planted in pots containing ready-made planting media in the greenhouse. Chlorophyll and carotenoid analyzes were performed at different plant ages from 1 to 11 weeks. The research design used is Completely Randomized Design. Data were analyzed using variance analysis and continued with Duncan test at 95% significance level. The results showed that the highest chlorophyll and carotenoid content was produced by the cowpea leaf in the vegetative phase or before the flowering time. The highest chlorophyll content was obtained at 4WAP (weeks after planting) of age crop, while the highest carotenoid content was obtained in 3WAP.